Strengthening Patients Safety Culture through the Implementation of SBAR Communication Method - Hilda Hilda; Rizky Setiadi; Emmy Putri Wahyuni; Supriadi Supriadi; Rina Loriana; Rasmun Rasmun; Evy Nurachmah (Humanistic Network for Science and Technology (HNST), 2018)
The communication method of Situation, Background, Assessment, and Recommendation (SBAR) are effective communication techniques that aim to improve patient safety. This study aims to analyze the application of SBAR communication to nurses to improve the safety culture of patients who are part of the service at A.W. Sjahranie Hospital, Samarinda, Indonesia. This study used a cross-sectional design with a population of 452 people spread over 14 service units. The sample size was 77 people. Variables in this study were SBAR communication methods and patient safety culture. The instrument used to assess the application was the SBAR communication method in the form of an observation sheet for the procedure for reporting patients' conditions during handover while collecting data on variable patient safety culture used a questionnaire from the agency for Healthcare Research Quality (AHRQ). Data of SBAR communication technique variables were collected using the observation method, while the patient safety culture variable was collected by distributing patient safety culture questionnaires. Data were analyzed using a Chi-Square test. The results of this study showed that nurses who used the SBAR communication method had a better patient safety culture (p = 0.000). The conclusion is the SBAR communication method to nurses can use to improve patient safety culture in the hospital. Keywords: SBAR communication method, Patient safety culture